Revolutionary amnesia and the nature of prerogative power. (24th November 2022) - Kershaw, David
Abstract: What is the nature and source of prerogative power? Where does it come from and how was it created? British constitutional law makes several assumptions in these regards. It assumes that these powers are inherent in or intrinsic to the Crown and it assumes that these powers are common law powers, meaning that they are constituted or conferred by the common law. This article takes issue with these conceptions of the nature of prerogative power. It shows that the idea that prerogative powers are sourced in the common law is derived from the seventeenth century's theory of the ancient constitution; a theory famously advocated by Sir Edward Coke and embodied in his observation that "the King hath no prerogative but that which the law of the land allows him." However, as the article shows, this theory of the ancient constitution was not an accepted theory of law in the seventeenth century, but rather an intensely contested political theory. It occupied a battlefield of constitutional ideas along with theories of kingly power sourced in conquest and the divine. Moreover, although these theories disagreed about the source and extent of prerogative power, they all posited a protocorporate Crown wedded to dynastic succession. The article shows that, from the perspective of a corporate Crown, the Glorious Revolution of 1689 resulted in the effective dissolution or dormancy of the kingly corporation embodied in James II, requiring that the Crown and kingly power be remade anew in the United Kingdom's last "historically first" constitutional event. Through a close reading of the Bill of Rights and the proceedings of the Convention Parliament of 1689, the article evidences the statutory remaking of the Crown and prerogative powers and shows how from 1689 to today prerogative powers should be understood as a grander form of statutorily delegated power.